Menggagas Collaborative Governance untuk Pengelolaan Sampah yang Lebih Baik di Desa Bacem, Kabupaten Blitar - Wydha Mustika Maharani; Ferida Asih Wiludjeng; Aditya Aji Santoso (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
The increase in population without the support of adequate waste management facilities, such as the availability of Temporary Shelters (TPS), has caused the people of Blitar Regency to have the habit of throwing rubbish carelessly in rivers or the habit of burning rubbish. This can cause various negative impacts on the environment and health. This research highlights the importance of the "Bacem Berseri" Waste Bank program to create public awareness in managing waste in a healthier and more sustainable way. The aim of this research is to analyze the implementation of collaborative governance in waste management in Bacem Village, Sutojayan District, Blitar Regency. The research method used was descriptive qualitative, data collection was carried out through in-depth interviews with stakeholders, including Environmental Service officials, village heads, administrators of the "Bacem Berseri" Waste Bank, and local residents. Data analysis techniques include data collection, data condensation, data presentation, and drawing conclusions. The results of this research show that collaboration between parties, including government, society, NGOs and the private sector, can increase the effectiveness of waste management through collaborative governance mechanisms. Key findings include the importance of face-to-face dialogue, facilitative leadership, commitment to process, and shared understanding in increasing community participation and building trust. The Waste Bank system implemented has had a positive impact in reducing waste accumulation and providing financial benefits for residents. However, the challenge lies in efforts to increase public awareness in all RTs to participate actively.